EFFECT OF PUBLIC EXPENDITURE STRUCTURE ON ACHIEVING FINANCIAL SUSTAINABILITY IN THE IRAQI BUDGET FOR THE PERIOD 2005-2020 - Hanan Hussain Khudair; Prof. Khaleel Mohammed Shahab (Scholar Express Journals, 2023)
The current research aims to identify the importance of public spending, what is financial sustainability, and measure the impact of public spending on financial sustainability and the impact of the time variation of public spending on productivity. In order to reach the goal for which this research was prepared, urine models were relied upon in order to know the strength of the correlation and influence between the two variables. Several conclusions were reached, the most important of which is that the misdistribution of public spending during the fiscal year is one of the most important reasons that lead to a gradual decrease in the productivity of public spending, as the low percentage of public spending means an increase in its productivity in the first quarter, and the inflation of the volume of public spending at the end of the year leads to Low productivity. We also reached many recommendations, the most important of which was the development of a modern and sophisticated method for preparing budgets so that by linking the funds spent with the goals achieved, and thus identifying what is being achieved and the extent of the integrity of government units by committing to achieving the set goals.
Keywords: preparing; achieved; extent; government